Comparison of temperature of metamorphism using quartz c-axis fabric thermometer, Zr-in-rutile and Ti-in-quartz, using as example quartzite samples of the Carrancas Group, MG, Brazil - Araújo, Beatriz Pontes (2018)
Quartz is one of the most common minerals in the Earth\'s crust, and is an important constituent of many metamorphic rocks. Because of the correlation between the dynamic recrystallization mechanisms and temperature, it is possible to understand the relationship between deformation and metamorphism evolution with the investigation of quartz, its textures, crystallographic orientation and its trace elements composition. Recently, thermometer calibrations were proposed based on the relationship between c-axis fabric open angle. Studies show that trace elements are also reliable indicators for geothermometers, especially on rocks without metamorphic index minerals,, such as in quartzites. With these calibrations it is possible to investigate the metamorphic-deformational evolution and compare to the metamorphic evolution of associated rocks containing diagnostic paragenesis and P-T conditions, allowing the full picture of establishment of the relationship between deformation and metamorphism. The aim of this research is to evaluate the c-axis thermometer, using data from Universal Stage and Electron Backscatter Diffraction (EBSD), as well as trace elements thermometry, Ti-in-quartz and Zr-in-rutile. The study was conducted on quartzites of the Carrancas Group, on Serra da Estância, Serra do Pombeiro and Serra de Carrancas, which P-T conditions of metamorphism were established with great precision in previous works. The study area is located in the southern region of Minas Gerais, near the cities of Carrancas, Itutinga, Itumirim and Lavras. Temperatures obtained by the c-axis thermometer were confronted with previously processed data and produced different results for each method, Universal Stage and EBSD. The Universal Stage produced a temperature that fits very well with metamorphic peak from previously calculated temperatures, and it seems to be a very reliable, cheap and relatively fast method. The stereograms made with EBSD data produced blurred girdles. It is not clear if the acquired data was either made properly or if this is a result of superimposed events of deformations, as suggested by petrography. The Zr-in-rutile thermometer partially agrees with the thermobarometry results of the literature, because at temperatures below 600 °C, it does not activate the zircon to participate on cation exchange reactions with other minerals, so the Zr concentration on rutile is considered to be from the source rock, and not related to deformation or metamorphism. The Ti-in-quartz was not a reliable thermometer for this case study. The temperatures are higher than the expected and the hypothesis is that the quartz grains might not have enough energy to exchange cations with rutile and zircon during the deformation and metamorphism caused by shear zones on Carrancas klippe. For further investigation, it is interesting to use cathodoluminescence that might map the Ti concentration zones on quartz grains to identify portions with different Ti concentrations and investigate their relationship with possible recrystallization textures.